Curative resection of an aldosteronoma causing primary aldosteronism in the second trimester of pregnancy - Shekhar, Skand (Endocrinol Diabetes Metab Case Rep, 2020)
SUMMARY: A 29-year-old primigravida woman with a known history of primary aldosteronism due to a right aldosteronoma presented with uncontrolled hypertension at 5 weeks of estimated gestation of a spontaneous pregnancy. Her hypertension was inadequately controlled with pharmacotherapy which lead to the consideration of surgical management for her primary aldosteronism. She underwent curative right unilateral adrenalectomy at 19 weeks of estimated gestational age. The procedure was uncomplicated, and her blood pressure normalized post-operatively. She did, however, have a preterm delivery by cesarean section due to intrauterine growth retardation with good neonatal outcome. She is normotensive to date. LEARNING POINTS: Primary aldosteronism is the most common etiology of secondary hypertension with an estimated prevalence of 5–10% in the hypertensive population. It is important to recognize the subtypes of primary aldosteronism given that certain forms can be treated surgically. Hypertension in pregnancy is associated with significantly higher maternal and fetal complications. Data regarding the treatment of primary aldosteronism in pregnancy are limited. Adrenalectomy can be considered during the second trimester of pregnancy if medical therapy fails to adequately control hypertension from primary aldosteronism.